Implementación de una guía para el diagnóstico de fallas y estimación de eficiencia de máquinas eléctricas asíncronas utilizando el equipo MCEMAX (2019)
Maintenance as a system plays an important role to ensure continuous operation of equipment in production processes, cutting costs, increasing performance, and optimizing the quality of the product or service offered. That is why it is essential for industries today to carry out predictive maintenance activities or in the last corrective instances. This document presents a review and classification of the techniques implemented by the MCEMAX equipment to diagnose the six fault zones in asynchronous rotary electric machines, after conducting this research it is evident the importance of the execution and anticipated diagnosis of each failure from some practical cases, after carrying out this investigation, the importance of the execution and anticipated diagnosis of each failure is evident from some practical cases. The work is complemented with the analysis of the characteristics offered by the use of MCEMAX equipment for the estimation of efficiency in induction electric motors, through tests carried out in the electrical laboratory of the Universidad Autónoma de Occidente, where the reliability of MCEMAX equipment in this measurement was evaluated, through the contrast of the results of the tests used by the different methods and the results obtained by the MCEMAX equipment. Finally, a guide is made for the diagnosis of faults and estimation of efficiency of electrical machines using the MCEMAX equipment, which aims to direct the user regarding the functions, use and details of each test performed by the equipment, additionally supported with some examples of diagnosis already performed.